The Last Day of Oppression, and the First Day of the Same : the Politics and Economics of the New Latin American Left. - Webber, Jeffery R. (Haymarket Books, 2017)
This book offers an overarching political and economic evaluation of the Latin American Left between the late 1990s and 2016.